2013
DOI: 10.1063/1.4817376
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of electronic and structural properties of polycrystalline and epitaxial magnetron-sputtered ZnO:Al and Zn1-xMgxO:Al Films—Origin of the grain barrier traps

Abstract: Homoepitaxial and heteroepitaxial ZnO, ZnO:Al, and Zn1-xMgxO:Al films have been grown by magnetron sputtering from ceramic targets at substrate temperatures between 200 °C and 500 °C. We studied the relation between the electronic transport and structural properties for the epitaxially grown films and compared it to the properties of polycrystalline films by means of X-ray diffraction, transmission electron microscopy and optical reflectance and transmittance measurements. The results show that the epitaxial g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 52 publications
3
24
0
Order By: Relevance
“…This again is an indication that additional effects influence the electrical transport in ZnO films directly at the interface. As already shown earlier for ZnO:Al films, 33 we confirmed that the electrical film properties are quite insensitive to the crystallographic film structure, i.e., to preferred orientation, grain size and even polycrystalline or epitaxial growth. This means, after the coalescence of the nucleating islands the resistivity of the films is almost constant.…”
Section: Electrical Properties Of Azo and Ito Filmssupporting
confidence: 86%
“…This again is an indication that additional effects influence the electrical transport in ZnO films directly at the interface. As already shown earlier for ZnO:Al films, 33 we confirmed that the electrical film properties are quite insensitive to the crystallographic film structure, i.e., to preferred orientation, grain size and even polycrystalline or epitaxial growth. This means, after the coalescence of the nucleating islands the resistivity of the films is almost constant.…”
Section: Electrical Properties Of Azo and Ito Filmssupporting
confidence: 86%
“…7). In particular, the lowest FWHM rc (i.e., $2.6 found for jV d j ¼ 56 V sample) compared well with the best value of magnetron sputtered polycrystalline AZO films (2.5 , RF deposition at 250 C), 30,31 indicating high crystallinity of our films. 8.…”
Section: Structural Characterizationsupporting
confidence: 68%
“…Two types of FWHM values were obtained: one from the conventional h-2h scans (FWHM 2h ) and the other from the rocking curve scans (FWHM rc ). 30,32 Actually, for a high density of carriers (>10 20 cm À3 ) in polycrystalline degenerate semiconductors, their mobility is dominated by ionized impurity scattering, not by grain boundary scattering. 10), with the lowest values found in the optimal jV d j window.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…Instead of q opt , most authors compute the mobility l opt . [29][30][31][32][33][34][35][36][37][38][39][40] The determination of l opt by modeling of optical spectra requires the effective mass m*, whereas the resistivity q opt can be evaluated without knowing m*. As the effective mass is prone to considerable uncertainties, 30,35,36,40 we will focus on the resistivity q opt .…”
Section: Methodsmentioning
confidence: 99%